2020
DOI: 10.2196/23520
|View full text |Cite
|
Sign up to set email alerts
|

Association Between LGB Sexual Orientation and Depression Mediated by Negative Social Media Experiences: National Survey Study of US Young Adults

Abstract: Background Lesbian, gay, and bisexual (LGB) persons are disproportionately affected by depression and have high social media use rates. Negative social media experiences may modify depressive symptoms among LGB persons. We sought to assess the potential influence of negative social media experiences on the association between LGB orientation and depression. Objective The aim of this study was to assess the potential influence of negative social media ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…These characteristics highlight the potential of leveraging social media to deliver interventions that provide information and support to rural-living LGBTQ youth ( 25 ). However, social media can also be a conduit for rejection, discrimination, bullying, and other negative experiences, potentially increasing social isolation and risk for negative mental health outcomes ( 26 , 27 ). While there is research focused on understanding individual- and community-level needs of social support among rural-living LGBTQ youth, ( 2 , 11 , 28 ) little is known about the potential of leveraging social media for interventions seeking to provide support and reduce perceived isolation among this group ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics highlight the potential of leveraging social media to deliver interventions that provide information and support to rural-living LGBTQ youth ( 25 ). However, social media can also be a conduit for rejection, discrimination, bullying, and other negative experiences, potentially increasing social isolation and risk for negative mental health outcomes ( 26 , 27 ). While there is research focused on understanding individual- and community-level needs of social support among rural-living LGBTQ youth, ( 2 , 11 , 28 ) little is known about the potential of leveraging social media for interventions seeking to provide support and reduce perceived isolation among this group ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gay Lesbian Straight Education Network [ 4 ] found that 42% of LGBTQ youth aged 13-18 years had been harassed on the internet, whereas 32% reported being sexually harassed on the internet; these percentages were significantly lower (15% and 8%, respectively) among non-LGBTQ youth. More recently, researchers have suggested that there is a relationship between the negative social media experiences of young sexual minority adults and their depressive symptoms [ 45 ]. Qualitative research has also examined the experiences of sexual minority youth with cyber-victimization, finding that it is often related to, although less common than, in-person harassment [ 38 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Seeking feedback on SNSs has been linked to reduced self-esteem ( 51 ) and depressive symptoms, especially when self-worth depends on online feedback ( 26 , 52 ). In addition, a current study suggested that the higher rates of depressive symptoms in LGBTQ persons could to some extent be explained by their exposure to negative experiences on social media including being called out or hurt, receiving negative or no feedback, and being excluded ( 53 ).…”
Section: The CI As An Implicit Learning Environment and Its Implicati...mentioning
confidence: 94%